Surface-Degradable Drug-Eluting Stent with Anticoagulation, Antiproliferation, and Endothelialization Functions - Ruixia Hou; Leigang Wu; Jin Wang; Zhilu Yang; Qiufen Tu; Xingcai Zhang; Nan Huang (Biomolecules, 2019)
Drug-eluting stents (DES) have been widely applied for saving the life of patients with coronary artery diseases (CADs). However, conventional polymers such as polylactic acid (PLA) and poly (lactic-co-glycolic acid) (PLGA), which are widely applied for drug-eluting stents studies, have serious bulk erosion problems, like high local acidity and poor mechanical properties. Instead, we chose surface erosion polymer poly (1, 3-trimethylene carbonate) (PTMC) as a drug carrier in this study. Here, we fabricated and characterized a novel durable-polymer drug-eluting 316 L stainless steel (SS) stent, in which the inner surface was coated with a Ti⁻O film using the magnetron sputtering method to promote the growth of endothelial cells (ECs). On the outer layer of the stent, first, a Ti⁻O film was deposited and, then, on top of it a rapamycin-loaded PTMC coat was deposited using the ultrasonic atomization spray method. This dual coating inhibited the migration and expansion of smooth muscle cells (SMCs). The drug coating also inhibited the adhesion/activation of platelets. In tests on dogs, it was found the novel stent promoted re-endothelialization and reduced restenosis, in contrast to the plain SS stent. Thus, the novel stent may have promise for use in treating patients with CAD.